1994
DOI: 10.1183/09031936.94.07081425
|View full text |Cite
|
Sign up to set email alerts
|

Increased PMA-induced chemiluminescence from whole blood of patients with bronchial hyperreactivity

Abstract: Blood phagocytes from patients with asthma have an increased capacity to produce reactive oxygen metabolites. We studied whether whole blood luminol-dependent chemiluminescence could detect this phenomenon in patients with a normal spirometry but bronchial hyperreactivity as determined with a methacholine bronchial challenge test. Whole blood chemiluminescence, serum eosinophilic cationic protein (ECP), and serum myeloperoxidase (MPO) were determined from 50 patients referred for a methacholine challenge due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The ability of these cells to generate highly reactive oxygen species (ROS), including super-oxide anion, following activation of a membraneassociated reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is an important part of the host defence system, and has also been implicated in inflammation in a variety of pulmonary diseases [2,3], including asthma [4,5]. Oxygen metabolites cause tissue injury, smooth muscle contraction, increased airway vascular permeability, and may increase airway responsiveness and release of var-ious mediators [4].…”
mentioning
confidence: 99%
“…The ability of these cells to generate highly reactive oxygen species (ROS), including super-oxide anion, following activation of a membraneassociated reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is an important part of the host defence system, and has also been implicated in inflammation in a variety of pulmonary diseases [2,3], including asthma [4,5]. Oxygen metabolites cause tissue injury, smooth muscle contraction, increased airway vascular permeability, and may increase airway responsiveness and release of var-ious mediators [4].…”
mentioning
confidence: 99%
“…The agonist, fMLP binds to specific G-protein-linked formyl peptide receptors on the cell membrane, initiating a cascade of reactions starting with the activation of phospholipase C (PLC) leading to activation of PKC, which in turn activates NOX. Although all the phagocytes are present in the whole blood sample, the luminescence signal obtained in whole blood is a function of the quantity and activity of neutrophils (Ristola & Repo, 1989), and is also indicative of their metabolic activity (Nordman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Estonian part of the ECRHS, the methacholine challenges were performed with the Spira Elektro‐2 dosimeter. This dosimeter method with controlled tidal breathing has been used widely in clinical practice and research ( Nieminen et al ., 1988 ; Nieminen, 1992; Nordman et al ., 1994 ; Hedman et al ., 1996 ). In previous studies, both dosimeters have shown good repeatability in estimating the provocative dose of methacholine producing a 20% fall in forced expiratory volume (FEV) in 1 s (PD 20 ).…”
Section: Introductionmentioning
confidence: 99%